2012
DOI: 10.1521/jscp.2012.31.8.835
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Interpersonal Self-Support and Depression: A Longitudinal Study

Abstract: Previous cross-sectional studies have found that most traits of interpersonal selfsupport (iSS) were associated with depression symptoms, but longitudinal studies have been lacking. the interpersonal Self-Support Scale for adolescent Students (iSSS-aS) and the Self-rating Depression Scale (SDS) were administrated twice over a six month interval to 427 participants recruited from five universities. Cross-lagged path analysis revealed that depression at time 1 significantly negatively predicted the five iSS subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Recent research also reported that this scale had an adequate internal reliability and was converged with other self-report assessments of depression, such as the Depression Adjective Check List, the Brief Symptom Inventory, and the Major Depression Scale (Thurber et al, 2002). Therefore, the SDS has also been used in research about depression and perfectionism (Di Schiena, Luminet, Philippot, & Douilliez, 2012;Julal, 2013;Xia, Ding, Hollon, & Fan, 2012;Zi & Zhou, 2007). In our sample, the Cronbach's alpha coefficient for internal reliability was 0.85.…”
Section: Measuring Individual Anxiety and Depressionmentioning
confidence: 99%
“…Recent research also reported that this scale had an adequate internal reliability and was converged with other self-report assessments of depression, such as the Depression Adjective Check List, the Brief Symptom Inventory, and the Major Depression Scale (Thurber et al, 2002). Therefore, the SDS has also been used in research about depression and perfectionism (Di Schiena, Luminet, Philippot, & Douilliez, 2012;Julal, 2013;Xia, Ding, Hollon, & Fan, 2012;Zi & Zhou, 2007). In our sample, the Cronbach's alpha coefficient for internal reliability was 0.85.…”
Section: Measuring Individual Anxiety and Depressionmentioning
confidence: 99%
“…For example, no Western personality concept similar to interpersonal flexibility was found to be associated with either enacted or perceived social support (Xia et al., 2012). In addition, although interpersonal independence and interpersonal responsibility were both negatively correlated with sociotropy, they each could predict depression even after controlling for sociotropy (Xia et al., 2011b). Presumably, interpersonal self‐support overlaps in some respects with Western personality traits, but it also brings some new constructs beyond traditional Western personality traits.…”
Section: Interpersonal Self‐supportmentioning
confidence: 99%
“…Interpersonal responsibility is a recently proposed interpersonal trait that originated from the Chinese traditional culture and refers to being faithful and truthful to others ( Xia, 2010 ; Xia et al, 2014a ). It was found to be a protective personality factor of mental health and is beneficial for social communication ( Xia et al, 2012a , b, 2014b ). Hostility and aggression are always regarded as two of the psychological symptoms and negative social behaviors ( Dodge, 1980 ; Ullrich et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, interpersonal responsibility was found to be negatively correlated with the hostility subscale of the Symptom Check List-90 (SCL-90) ( Xia, 2010 ) and proactive and reactive aggression ( Wu, 2016 ). Moreover, the relational schema is regarded as an important cognitive unit of interpersonal responsibility ( Xia et al, 2012a ). Individuals with high interpersonal responsibility usually have positive interpersonal attitudes toward others, whereas individuals with low interpersonal responsibility difficultly disengage from negative interpersonal information ( Xia et al, 2014a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation